A comparative analysis of retrospective records of antibiotic usage in patients before and after surgery in a tertiary care government hospital in Delhi - Arora, Tarun; Bhowmick, Samya; Singh, Jasbir (International Journal of Research in Medical Sciences, 2024)
Background: Antimicrobial resistance (AMR) is major problem in most of countries worldwide. Antimicrobial Stewardship program (AMSP) encourages both government and private hospitals in country to bring out guidelines regarding antimicrobial usage and hospital infection control (HIC). However, it is still in nascent stage. A retrospective study to generate lacking data about usage of antibiotics in inpatient settings in a government hospital. Methods: Retrospective records of antibiotic usage in adult patients before and after surgery admitted in department of surgery, LHMC and Smt. Sucheta Kriplani hospital, New Delhi. The prescribed doses were converted to a number as per WHO defined daily dose (DDD) of each antibiotic and presented as per ATC/DDD methodology. Results: The records of 121 patients admitted between June 2021 to February 2022 were retrieved. Ceftriaxone, was the leading choice of antibiotic both pre and post operatively, while co-amoxyclav was second most preferred antimicrobial. Mean ± SD for DDD pre-op and post-op was 3.345±1.602 with p<0.001 which was highly significant. Mean ± SD for average duration of stay pre-op and post-op was 3.041±1.179 with p<0.01 which was significant. Only 16 patients had complications before, during or after the procedure which prolonged their stay in hospital. There were no procedure related deaths till last follow up. Conclusions: Guidelines for selection of proper antimicrobial usage in peri-operative period were not consistent. We advocate evidence-based pre-operative and post-operative antibiotic prophylaxis practices and rational antibiotic usage depending on prevailing antibiogram.